Blockchain-based Electronic Health Record Management System - Shrestha, Sulav; Panta, Sagar (Journal of Artificial Intelligence and Capsule Networks, 2023)
The Blockchain-based Electronic Health Record (B-EHR) system represents a significant advancement in healthcare data management. Concerns over data confidentiality and security have become increasingly critical in the healthcare sector, given the need for immediate data accessibility. Traditional centralized systems face accessibility issues, necessitating a transformative solution, and blockchain technology emerges as a promising candidate. This research introduces a patient-controlled, blockchain-based system that efficiently manages and safeguards individuals' health-related data. By harnessing the Ethereum network and utilizing tools such as Ganache, Solidity, and web3.js, this system takes a systematic approach to overcome the limitations of centralized systems. Smart contracts, the basis of blockchain technology, serve as the backbone for storing and processing patients' data in a decentralized manner. Transactions are conducted securely through these smart contracts, ensuring patient privacy and data security. Notably, any modifications to transactions can be verified and propagated across the entire distributed network, enhancing data integrity. Complementing this system is a cryptocurrency wallet like MetaMask, providing a centrally controlled repository where records can be swiftly accessed and secured by authorized individuals, including doctors and patients. This integration significantly improves data accessibility and security within the healthcare domain. Ultimately, this research aims to leverage blockchain technology for simultaneous data retrieval, enhancing efficiency, credibility, and accessibility. It offers a robust framework for securely storing data with tailored access permissions and facilitates the safe transfer of patient medical records. In essence, it introduces a swift and secure health record system and an innovative protocol, promoting greater transparency and ownership of sensitive data in the healthcare sector through blockchain integration.
Keywords: Electronic Health Record; Ethereum; MetaMask; Blockchain; Decentralization; cryptocurrency wallet